Termination of employment relationship in uniformed services in connection with their reorganisation or dissolution – constitutional issues (Ius Novum, 2024)
This article addresses the legal issues arising from the transformation of internal security bodies within the structure of public administration, specifically focusing on how such events impact the service relationship of officers employed in those structures (the so-called ‘uniformed services’). The analysis covers regulations governing the service relationships of officers in the State Protection Office, Government Protection Bureau, and Customs Services in connection with the dissolution of these institutions and the establishment of the Internal Security Agency, the Intelligence Agency, the State Protection Service, and the Customs and Fiscal Service. Theoretical and legal models are identified, and substantive legal provisions are presented to assess their compliance with the relevant provisions of the Constitution of the Republic of Poland.